2019
DOI: 10.1002/slct.201900040
|View full text |Cite
|
Sign up to set email alerts
|

NLO‐Phoric Emissive Quinoxaline Analog of Quinoline Yellow 54 and Z‐Scan Studies

Abstract: Quinoxaline derivative QY 54 A, an analog of commercially available C.I. (Colour index) Disperse Yellow 54 (quinoline derivative) is synthesized and confirmed by 1 H, 13 C NMR, LC-MS, and CHN analysis. It is emissive (512 nm) with a quantum yield (φ F ) = 0.34. The electrochemical properties of both the dyes were investigated using cyclic voltammetry (CV). The titled dyes are thermally stable (up to 350°C). A comprehensive study of linear and nonlinear optical (NLO) properties of commercial dye (QY 54) and its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…The charge transfer phenomenon i. e. ICT can also be determined with bond length alteration in benzene rings which is expressed by the normalized quinoid character. [66] The δr for VA(1-2) and VI(1-2) (see Figure 10) is calculated using equation 1.…”
Section: Quinoid Character (δR)mentioning
confidence: 99%
See 2 more Smart Citations
“…The charge transfer phenomenon i. e. ICT can also be determined with bond length alteration in benzene rings which is expressed by the normalized quinoid character. [66] The δr for VA(1-2) and VI(1-2) (see Figure 10) is calculated using equation 1.…”
Section: Quinoid Character (δR)mentioning
confidence: 99%
“…DFT method is a dynamic tool to calculate NLO properties, [11,[67][68][69][70][71] but their accuracy is found to be very sensitive to the choice of the functionals. [66] Therefore to get reliable information of the NLO properties, selection of proper functional is crucial. [72] The NLO properties of all dyes were calculated by employing hybrid functionals i. e. B3LYP (20 % HF exchange) and BHandHLYP (50 % HF exchange) and rangeseparated hybrid functionals i. e. CAMB3LYP (19-65 % HF exchange), ωB97 (0-100 % HF exchange), ωB97X (15-100 % HF exchange) and ωB97XD (22-100 % HF exchange) having different percentage of Hartree-Fock (HF) exchange.…”
Section: Non-linear Optical Properties Estimated By a Quantum Chemicamentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, theoretical estimation of NLO properties of complex organic molecules to establish the influence of individual moieties with aid of DFT calculation are under recent attraction. Various molecular structural parameters, molecular electrostatic potential map, charge transfer interaction and NLO property of various molecules were analysed by DFT method and using Natural bond orbital analysis . Notable report includes the establishment of role of halogen substituents in tuning the NLO properties of cycloparaphenylenes (CPP) and theoretical estimation shows high NLO values was obtained when one half of each CPP was substituted in halo CPP .…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive study of linear and nonlinear optical properties of quinoxaline and its analogue Quinoline Yellow 54 was performed by the Z‐scan technique and DFT. It was reported that by a small structural change from CH to N atom in QY 54 core led to emissive analogue QY 54 A with enhanced ICT for better NLO properties . The intra‐molecular charge transfers from natural bonding orbital analysis of newly synthesized NLO material ethyl4‐(3‐(1,3‐dimethyl‐1H‐pyrazole‐5‐carboxamido) phenyl)‐ 1,2,3,4‐tetrahydro‐6‐methyl‐ 2‐oxopyrimidine‐5‐carboxylate was made using TD‐DFT calculations .…”
Section: Introductionmentioning
confidence: 99%